PENGEMBANGAN BUKU CERITA BERBASIS HEYZINE FLIPBOOK DALAM MENINGKATKAN KESADARAN PENCEMARAN LINGKUNGAN DI WILAYAH PESISIR - Ain Yusuf, Nur; Nusantari, Elya; Sidik Katili, Abubakar; Susanti Hamidun, Marini; Nur Akbar, Muh. (Universitas Cokroaminoto Palopo, 2025)
This research aims to develop a storybook based on Heyzine Flipbook as an interactive learning medium to increase students' awareness of environmental pollution in coastal areas. The research was carried out in class X1 of SMA Negeri 2 Tilamuta using the ADDIE development method which includes analysis, design and development stages. Digital storybooks are developed by integrating attractive illustrations, animations and interactive displays that are easily accessible via various electronic devices. The validation results by media and materials experts show that the storybook meets the valid criteria with an average score of 80% to 100%. The practicality test was carried out through a questionnaire given to teachers and students. The results show that teachers gave an average rating of 96% and students gave an average rating of 97%, both in the very practical category. In addition, the implementation of learning during the two meetings showed an implementation level of 100% for all aspects observed, including opening, main, closing activities, class atmosphere, and time management. Teacher and student responses show that this storybook is able to increase interest, understanding and active involvement in the learning process. Thus, storybooks based on Heyzine Flipbook have proven to be effective and suitable for use as innovative learning media to foster environmental awareness in students. This product also supports strengthening the character of Pancasila students, especially in the aspects of caring for the environment and critical thinking.